The Impact of Abolishing the National Examination and the Role of the Minimum Competency Assessment on Students' Learning Motivation in Madrasah Islamiyyah: Implications for the Design of the Islamic Education Curriculum - Gustiva Andri Andri; Muhammad Auwal Yakubu (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: The Impact of Abolishing the National Examination and the Role of the Minimum Competency Assessment on Students' Learning Motivation in Madrasah Islamiyyah: Implications for the Design of the Islamic Education CurriculumObjective: This study aims to analyze the impact of the abolition of the National Exam (Ujian Nasional, UN) and the role of the Minimum Competency Assessment (AKM) on student learning motivation in Madrasah Islamiyyah and implications for Islamic education curriculum design. Methods: This research uses descriptive qualitative methods and data collection through interviews, observation, and documentation. Data analysis using the Miles and Huberman model. Results: The abolition of the National Examination and the implementation of AKM increase students' learning motivation because AKM assessment is more relevant to students' real abilities. However, challenges remain in curriculum adaptation as in Islamic education. Conclusion: Effective implementation of the abolition of the national exam and the implementation of IMR requires curriculum adaptation, especially in Islamic education, to increase student learning motivation. Contribution: This study contributes to the development of education policy by utilizing IMR to improve education quality and student motivation, as well as a reference in designing a more relevant and adaptive Islamic education curriculum. INDONESIAN: Dampak Penghapusan Ujian Nasional serta Peran Asesmen Kompetensi Minimum terhadap Motivasi Belajar Siswa di Madrasah Islamiyyah: Implikasi terhadap Desain Kurikulum Pendidikan IslamTujuan: Penelitian ini bertujuan untuk menganalisis dampak penghapusan Ujian Nasional (UN) dan peran Asesmen Kompetensi Minimum (AKM) terhadap motivasi belajar siswa di Madrasah Islamiyyah dan implikasi terhadap desain kurikulum pendidikan islam. Metode: Penelitian ini menggunakan metode deskriptif kualitatif, pengmpulan data melalui wawancara, observasi, dan dokumentasi. Analisi data menggunakan model Miles dan Huberman. Hasil: Penghapusan Ujian Nasional dan penerapan AKM meningkatkan motivasi belajar siswa, karena penilaian AKM lebih relevan dengan kemampuan nyata siswa. Namun, tantangan tetap ada dalam adaptasi kurikulum seperti dalam pendidikan islam. Kesimpulan: Implementasi Penghapusan Ujian Nasional dan penerapan AKM yang efektif memerlukan penyesuaian kurikulum khususnya dalam pendidikan islam dalam meingkatkan motivasi belajar siswa. Kontribusi: Penelitian ini berkontribusi dalam pengembangan kebijakan pendidikan dengan memanfaatkan AKM untuk meningkatkan kualitas pendidikan dan motivasi siswa, serta sebagai acuan dalam merancang kurikulum pendidikan Islam yang lebih relevan dan adaptif.